2015
DOI: 10.1007/s00040-015-0429-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of honey load by honeybee pollen foragers departing from the hive: the effect of pollen load size

Abstract: Honeybee foragers load a small amount of honey into the crop when they leave the hive. This ''honey at departure'' is used as a material to build pollen loads (glue honey) as well as fuel during flight in pollen foragers. We investigated the relationship between the size of pollen loads that a forager collected and the amount of honey at departure in the Western honeybee, Apis mellifera. Dancing pollen foragers increased honey at departure with the size of collected pollen loads. Analysis of the waggle-run dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Previous studies showed that the amount of nectar that foragers carry from the nest is adjusted by several factors, including target food type (nectar or pollen), food-source distance, and reward variability (Beutler 1950(Beutler , 1951Harano et al 2013Harano et al , 2014Harano and Sasaki 2015;Tan et al 2015). The frequency of begging trophallactic contacts with nest mates (putative reception of nectar) is also reported to change, depending on food-source profitability and variability (Núñez 1970;Farina 1996;Farina 2001, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that the amount of nectar that foragers carry from the nest is adjusted by several factors, including target food type (nectar or pollen), food-source distance, and reward variability (Beutler 1950(Beutler , 1951Harano et al 2013Harano et al , 2014Harano and Sasaki 2015;Tan et al 2015). The frequency of begging trophallactic contacts with nest mates (putative reception of nectar) is also reported to change, depending on food-source profitability and variability (Núñez 1970;Farina 1996;Farina 2001, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Honeybee foragers tend to specialize in either nectar or pollen collection (Free 1960;Page 2013;Harano and Sasaki 2015). Pollen foragers not only use the nectar carried from the nest as fuel but also use it as "glue" to build pollen loads (Parker 1926;Hodges 1952).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations